Employer Branding Strategies to Attract Young Talent: A Systematic Literature Review and Conceptual Framework - Liuyan Zhang (Universitas Negeri Surabaya, 2026)
In an increasingly competitive labor market, attracting young talent—primarily from Generation Z and the younger millennial cohort—has become a strategic priority for organizations worldwide. Employer branding, defined as the package of functional, economic, and psychological benefits provided by employment and identified with the employing company, plays a pivotal role in this endeavor. This article presents a systematic literature review of employer branding strategies specifically aimed at attracting young talent, synthesizing findings from 42 peer-reviewed articles published between 2019 and 2024. Through thematic analysis, five core strategic dimensions emerged: (1) a compelling digital and social media presence, (2) an authentic Employee Value Proposition (EVP) emphasizing purpose, flexibility, and career growth, (3) employee-generated content and advocacy programs, (4) robust diversity, equity, inclusion, and sustainability commitments, and (5) a personalized, technology-enhanced candidate experience. The discussion integrates these dimensions into a conceptual framework, highlighting their interplay and the centrality of authenticity and value alignment for young professionals. The article concludes with practical implications for human resource practitioners and outlines avenues for future research.